Plasmon polariton and (n)= 0 non-Bragg gaps in superlattices with metamaterials (2011)
ABSTRACT: We consider one-dimensional photonic superlattices made up of alternate layers of a right-handed nondispersive material and a metamaterial with Drude-type dielectric permittivity and magnetic permeability. By thoroughly investigating the dispersion relation for the propagation of obliquely incident optical fields obtained from Maxwell’s equations and the transfer-matrix technique, we demonstrate that, in the long-wavelength limit, the dispersion is the same that one would obtain by considering a homogeneous effective medium with Drude-type responses at shifted electric and magnetic plasmon frequencies. Moreover, we show that the plasmon polariton and (n)= 0 non-Bragg gaps correspond to regions of the low-energy spectrum where the effective medium is absorptive, exhibiting an imaginary effective refraction index.